Community Compliance in the Use of Mosquito Nets for Malaria Prevention - Noviana, Ineke; Dian Christine Aprilianda Haba; Veronika Toru (Poltekkes Kemenkes Kupang, 2023)
Malaria is an acute, life-threatening febrile disease primarily found in tropical areas with Malaria endemicity. In 2023, East Sumba Regency became the second-highest Malaria case after Southwest Sumba. Malaria control efforts remain a primary target in achieving optimal public health and reducing Malaria incidence. One effort is the distribution of free long-term insecticide-treated bed nets. However, Malaria cases in Village X, the research location, are still relatively high. Community behavior and awareness significantly influence the use of bed nets, thereby reducing Malaria incidence. This study aims to determine the description of the community's existence in the use of bed nets. This type of research uses a quantitative research method. The sampling technique is Accidental Sampling. The instrument used is a questionnaire with a sample size of 30 respondents who meet the inclusion criteria. Where the questionnaire was distributed directly. Because this study is descriptive research, the data analysis technique is carried out by calculating the total compliance score, grouping the level of compliance (compliant and non-compliant), presenting data in the form of a frequency distribution table, and interpreting the results. The research was conducted in East Sumba Regency in village X. Based on the results of the study on 30 community respondents in the research area, data was obtained that most of the respondents were not compliant in using mosquito nets, namely 18 people (60%), while those who were compliant in using mosquito nets were 12 people (40%). This shows that the level of community compliance in using mosquito nets is still relatively low, because more than half of the respondents have not consistently used mosquito nets as an effort to prevent Malaria.